Factors influencing high accident rate among harvesters in oil palm plantation / Muhammad Hafiz Zakariah - Zakariah, Muhammad Hafiz (Faculty of Plantation and Agrotechnology, 2016)
This research is important to find out the factors affecting the rate of accident among harvesters in oil palm plantation during harvesting. There are several factors contribute to the rate of accidents among harvester in oil palm sector which are worker's attitude, worker's skill, management, tools and equipment and environment. A simple random technique was used to selected sample of 73 harvester who are working in oil palm sector at one of the estate in Paloh Hinai,Pahang. The questionnaire and interview session was done to the selected respondent. Correlation and regression analysis are use in this research to analyze the data by using Statistical Package for the Social Science (SPSS) software. From the analyzing process the relationship between independent factor and dependent factor were found. Based on the result, researcher found worker's attitude factor, worker's skill factor, tools and equipment factor and environment factor have significant relationship toward the rate of accident among harvester.